A unique measles B3 cluster in the United Kingdom and the Netherlands linked to air travel and transit at a large international airport, February to April 2014 - Nic Lochlainn, Laura; Mandal, Sema; de Sousa, Rita; Paranthaman, Karthik; van Binnendijk, Rob; Ramsay, Mary; Hahné, Susan; Brown, Kevin E. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2016)
This report describes a joint measles outbreak investigation between public health officials in the United Kingdom (UK) and the Netherlands following detection of a measles cluster with a unique measles virus strain. From 1 February to 30 April 2014, 33 measles cases with a unique measles virus strain of genotype B3 were detected in the UK and the Netherlands, of which nine secondary cases were epidemiologically linked to an infectious measles case travelling from the Philippines. Through a combination of epidemiological investigation and sequence analysis, we found that measles transmission occurred in flight, airport and household settings. The secondary measles cases included airport workers, passengers in transit at the same airport or travelling on the same flight as the infectious case and also household contacts. This investigation highlighted the particular importance of measles genotyping in identifying transmission networks and the need to improve vaccination, public health follow-up and management of travellers and airport staff exposed to measles.